Nano-magnetic CaO/Fe2O3/Feldspar catalysts for the production of biodiesel from waste oils - Hanif, Maryam; Bhatti, Ijaz Ahmad; Hanif, Muhammad Asif; Rashid, Umer; Moser, Bryan R.; Hanif, Asma; Alharthi, Fahad A. (Multidisciplinary Digital Publishing Institute, 2023)
Production of biodiesel from edible vegetable oils using homogenous catalysts negatively impacts food availability and cost while generating significant amounts of caustic wastewater during purification. Thus, there is an urgent need to utilize low-cost, non-food feedstocks for the production of biodiesel using sustainable heterogeneous catalysis. The objective of this study was to synthesize a novel supported nano-magnetic catalyst (CaO/Fe2O3/feldspar) for the production of biodiesel (fatty acid methyl esters) from waste and low-cost plant seed oils, including Sinapis arvensis (wild mustard), Carthamus oxyacantha (wild safflower) and Pongamia pinnata (karanja). The structure, morphology, surface area, porosity, crystallinity, and magnetization of the nano-magnetic catalyst was confirmed using XRD, FESEM/EDX, BET, and VSM. The maximum biodiesel yield (93.6–99.9%) was achieved at 1.0 or 1.5 wt.% catalyst with methanol-to-oil molar ratios of 5:1 or 10:1 at 40 °C for 2 h. The CaO/Fe2O3/feldspar catalyst retained high activity for four consecutive cycles for conversion of karanja, wild mustard, and wild safflower oils. The effective separation of the catalyst from biodiesel was achieved using an external magnet. Various different physico-chemical parameters, such as pour point, density, cloud point, iodine value, acid value, and cetane number, were also determined for the optimized fuels and found to be within the ranges specified in ASTM D6751 and EN 14214, where applicable.